Woman Domination: A Study Of Taylor Jenkins Reid’s The Seven Husbands Of Evelyn Hugo - Syifa Kartika Aristawidya (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This examines the theme of woman domination in Taylor Jenkins Reid's novel,